Hamstring Injuries: A Comprehensive Review of Current Treatment Options - Górka, Piotr; Frączek, Julia; Borówka, Karolina; Swoboda, Kamil; Wiater, Zuzanna; Włodarczyk, Aleksandra; Brankowska, Karolina; Jakubowska, Marta; Kądziołka, Witold; Domagała, Szymon (Quality in Sport, 2026)
Background: Hamstring muscle injuries (HMI) remain the most prevalent non-contact injury in high-speed sports, particularly football and athletics. Despite sports medicine advancements, HMI is characterised by high recurrence rates (12–33%), causing significant time loss and performance decrements. Aim: This paper provides a comprehensive literature review regarding the functional anatomy, risk factors, diagnostic classification, and evidence-based treatment strategies for HMI. Material and methods: A narrative literature review was conducted using PubMed and MEDLINE. We focused on high-quality studies (systematic reviews, randomised controlled trials, clinical guidelines) published between 2010 and 2025, covering conservative and surgical management. Results: The biceps femoris long head's bi-articular architecture and dual innervation predispose it to eccentric strain during sprinting. Diagnosis has evolved with the British Athletics Muscle Injury Classification (BAMIC), which identifies intratendinous involvement as predicting prolonged recovery. Conservative management remains the gold standard for mid-substance injuries; L-protocol (lengthening) and eccentric strengthening show superior outcomes over concentric training. Surgery is indicated for complete proximal avulsions or high-grade partial tears with retraction (>2 cm); acute repair yields better outcomes than chronic reconstruction. Conclusions: Effective HMI management requires a multimodal approach. While conservative care resolves most injuries, precise MRI diagnosis is crucial to identify surgical candidates early. Return to play must be criteria-based, prioritising restored eccentric strength, fascicle length, and sprint mechanics over time-based protocols or imaging clearance.